La retroalimentación en la escritura universitaria en pandemia. El caso de estudiantes ingresantes a carreras de ciencias médicas en Chile - Vásquez-Rocca, Liliana (2024)
Amid the global COVID-19 pandemic, many countries, including Chile, implemented extensive lockdown measures, prompting universities to shift to remote teaching. While there has been substantial research on feedback in online education, few studies have considered the unique challenges posed by the pandemic. This research investigates the provision of feedback on university-level writing assignments for students pursuing medical sciences degrees during this unprecedented period. Using a quantitative approach, the study involved 341 university students who completed a self-administered questionnaire. The analysis of the results revealed several key findings: a) feedback processes had an effective initial phase, b) educators were less likely to provide feedback during intermediate stages, and c) feedback primarily focused on lexical-grammatical aspects, mirroring traditional face-to-face contexts.